Exploring the access and influence of Edu TV and radio programs on the learners' self-directed learning among the grade 12 learners enrolled on distance mode at Namibian College of Open Learning (NAMCOL ) - Nenghwanya, Erestine (School of Education, 2021)
This research study focused on the issue of access to flexible learning and the use of technology (radio and TV) to assist in the learning process. The study was aimed at measuring the influence of these technology services among grade 12 learners enrolled on distance mode at Namibia College of Open Learning (NAMCOL). The majority of distance education systems around the world have the same general structure of guiding students, which are based primarily on student-centered learning that demands a learner to work independently. Regular lecturing facilities for distance learners are only possible in scheduled workshops at study centers. These provisions are however, inconvenient since most distance learners are working people, as well as inadequate to provide the necessary educational guidance to distance learners. In situations where regular interaction between teacher and student is limited or not possible, the media plays a vital role in providing educational assistance to these learners. NAMCOL, as an institution, has embraced the concept of utilizing media to assist distance learners with programs such as Edu TV and Radio Programmes as well as Online resources. Self-directed learning theories and Malcolm Knowles's theory of Andragogy were used as the theoretical frameworks for the study. In exploring access and influence of Edu TV and radio program on the learner's self-directed learning among the grade 12 learners enrolled at distance mode at Namibian College of Open Learning (NAMCOL), the researcher employed several research strategies to measure the influence that flexible programs have on learners. The research strategies employed in the study included questionnaires and interviews, which were used to yield both qualitative and quantitative research data. The main findings of the study were that the flexible learning policy implemented by NAMCOL is proving successful in affording distance learners access to Edu TV and radio program services. All participants indicated that the lessons were informative. Furthermore, it helps learners to assume responsibility for their learning. However, additional efforts from all stakeholders are required to keep up with the ever-expanding demand for ODL platforms. The study further revealed that implementing appropriate Andragogy fostered self-directed learning. In light of the findings of the research and the Andragogy applied, even though learners have access to the Edu programs, the lack of physical and appropriate technologies can impact negatively. For example, you can be self-directed, but if there are physical constraints and challenges in the pedagogy, the learners are demotivated to be self-directed.